PERBANDINGAN HASIL PENETAPAN KADAR VITAMIN C MANGGA DODOL DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-Vis DAN IODOMETRI - Karinda, Monalisa; Fatimawali, Fatimawali; Citraningtyas, Gayatri (PHARMACON, 2013)
ABSTRACTVitamin C is one of the nutrients that role as antioxidant and effectively overcome the freeradicals that can damage cells or tissue. Fruit is a good source of vitamin C, such as themango fruit. This study aimed to determine the levels of vitamin C in the mango fruit usingUV-Vis spectrophotometry method and Iodimetry method, and compare the results of bothmethods. Samples were identified as ripe mango. In this study, the levels of vitamin C wereanalyzed by using UV-Vis spectrophotometry and Iodimetry. The results of the analysis ofvitamin C in the mango dodol by using UV-Vis spectrophotometry is 15.88 g/100g, whereasthe content of vitamin C by using Iodimetry was 3.5 g/100g. From these results, showed thelevels of vitamin c by using the spektrofotometry uv-vis method is higher than the iodimetrymethod.Keywords: Vitamin C, mango, UV-Vis Spectrophotometry, Iodimetry.